Analysis of time efficiency in the implementation of a 2-story shophouse construction project on Jl. Pasundan Samarinda using the CPM (Critical Path Method) - Suramli, Suramli; Kurniawan, Angga Dwi; Wulandari, Eka (Institute of Computer Science (IOCS), 2025)
Delays in project execution are one of the main challenges that can significantly affect the cost and quality of the work results. This study aims to evaluate the time efficiency of the construction project of a two-story shop house on Jl. Pasundan, Samarinda by applying the Critical Path Method (CPM). This method is used to identify the critical path of the project, which is a series of activities that determine the shortest completion time of the project and have no time slack (float). This study applies a quantitative descriptive approach through case study methods, relying on primary data from interviews and field observations as well as secondary data in the form of project documents. The analysis shows that the project has a critical path in the order of activities A → B → C → D → E → F → G → H → L → M → N → O → P → Q, with a total working time of 108 days. Each activity on the critical path has a total float of zero, indicating that delays in these activities will directly affect the entire project schedule. The use of the CPM method in this project has proven successful in providing a comprehensive picture of time control and can serve as a basis for decision-making in medium-sized construction project management